Криометрические и термометрические исследования флюидных включений в кварце золоторудного месторождения Балка Широкая - Фомин, Ю.А.; Витык, М.О.; Демихов, Ю.Н.; Лазаренко, Е.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
The investigation of fluid inclusions for the gold deposit shows the evolution of the regres-sive mineral-forming system in the completed geological cycle. At the beginning of the cycle, the metamorphism destroyed inclusions of the volcanic stage and formed a new system of high-temperature inclusions rich in CO2 and CH4. The next tectonic-metasomatic activity transformed the system to the epithermal one revealed by rich liquid inclusions with gas and, sometimes, solid phases.